THE USE OF PODCAST AND INTERPRETIVE TASKS FOR PEER ASSESSMENT IN THE EXTENSIVE LISTENING CLASS - Delsa Miranty (International Conference on Education and Language (ICEL), 2016)
Effective learners have gained understanding of the individual and social processes necessary to learn how to learn. Since learning is an activity of making meaning construction not simply of receiving. The social dimension is always present, and in social contexts collaboration supports learning. Then, in the context of language education, listening is recognized as the first skill that learnt by the students in the EFL classroom. However, some problems are commonly found in the process of learning to listen the material in form of English. Students are usually less confident and often confuse to start to listen the material in the EFL classroom, especially in the extensive listening class. To minimize this problem, this study is aimed at discovering an alternative method in learning listening material by using Podcast and then the students discuss the material with their friends. So, by giving interpretative tasks then make a peer assessment  in the laboratory hopefully covered the students’ problem in the extensive listening class. Therefore, the teacher can also help the students to build their interaction skill and the students’ self confidence to improve their listening skill.